David O. Russell’s "Flirting with disaster". Survival of the family unit on the road - Induráin Eraso, Carmen (Huarte de San Juan. Filología y Didáctica de la Lengua, 2003)
lnstead of the usual denial of the responsibilities of domesticity —marriage, motherhood and employment— David O. Russell’s road comedy "Flirting with disaster" (1996) presents a family as road protagonist. The aim of this paper is to analyse the innovative appearance of the family unit in the road movie genre as presented in Flirting with Disaster, but specially to show the survival of the married couple and the happy family after the threat posed by the transformational road adventure. Despite its subversive depiction of controversial sex and gender issues through a successful comic perspective and its significant presentation of a companionate marriage and family as protagonists, Flirting with Disaster recovers Hollywood’s classical closure, regarding both form and content. lts traditional, unjustified promotion of marriage and the family may disappoint the viewer who may have found disaster as a more realistic option, more in accordance with the traditional conventions of the road movie genre.